Strengthening Spiritual Education Based on the Qur'ān in Building Character in the Digital Age - Karimullah, Suud Sarim; Kurniyadi; Mahrus; Moh Amin; Supriyadi; Ummu Diana Munawwarah (Green Publisher Indonesia, 2022)
This study aims to look at the effectiveness and influence of the Qur'ān on strengthening spiritual education for generations of Muslims in building character in the digital age because digital space can also become a spiritual space. This research is qualitative research that uses library research studies, and the data analysis technique used in this research is content analysis with the nature of descriptive-analytical research. Then the results of this study state that spiritual education is a part of education that has a strong influence on one's personality; make it inclined to goodness, adorned with noble qualities, hold fast in personality and behavior to noble character firmly and consistently. Strengthening spiritual education by living up to the character values in the Qur’ān will make humans become characters in the digital age with a complete sense of spirituality within themselves. Based on the Qur’ān, the spiritual education that is built can lead generations of Muslims to be intellectually, emotionally, and spiritually intelligent so that it can also lead to social intelligence.